2010
DOI: 10.4314/njsr.v8i1.54835
|View full text |Cite
|
Sign up to set email alerts
|

Waiting time among acute abdominal emergencies in a Nigerian teaching hospital: causes of delay and consequences

Abstract: Background-In many patients presenting with an acute surgical abdomen, the outcome of management is determined by the promptness of the appropriate surgical intervention. The average interval the patient has to spent waiting for treatment at first presentation to hospital with an acute abdominal emergency is unknown in our center. This study was designed to evaluate the waiting time between hospital presentation and operation,to highlight causes of the delay and outcome of treatment among patients admitted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
(16 reference statements)
3
14
3
Order By: Relevance
“…This result has a higher male to female ratio than that reported at Ibadan by Ajao 4. It is also in contrast with the finding from Sokoto by Mbah et al ,8 who reported intestinal obstruction as the commonest cause of acute abdomen.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This result has a higher male to female ratio than that reported at Ibadan by Ajao 4. It is also in contrast with the finding from Sokoto by Mbah et al ,8 who reported intestinal obstruction as the commonest cause of acute abdomen.…”
Section: Discussioncontrasting
confidence: 76%
“…This may be the result of increase in the number of laparotomy being performed over the years. In Sokoto, however, post-operative adhesions were not found to be a significant cause of intestinal obstruction in the study by Mbah in 2006 8. Also, the study differs from the report by Ajao4 in which intussusception was the second leading cause of intestinal obstruction.…”
Section: Discussioncontrasting
confidence: 54%
“…A total of 37 articles published from Nigeria in relation to various waiting times were found from the search and fulfilled the inclusion criteria 78910111213141516171819202122232425262728293031323334353637383940414243. A total of 11 publications (29.7%) were related to emergency surgery waiting times,7891011121314151617 10 (27%) were related to clinic waiting times,32333435363738394041 9 (24.3%) were related to day case surgery,232425262728293031 2 (5.5%) were related to investigation waiting times4243 and only 5 (13.5%) articles were specifically published on elective surgery waiting times 1819202122.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 publications (29.7%) were related to emergency surgery waiting times,7891011121314151617 10 (27%) were related to clinic waiting times,32333435363738394041 9 (24.3%) were related to day case surgery,232425262728293031 2 (5.5%) were related to investigation waiting times4243 and only 5 (13.5%) articles were specifically published on elective surgery waiting times 1819202122. A total of 9 articles (24.5%) were published from obstetrics and gynaecology (OG), 7 (19%) from general surgery, 5 (13.5%) from public health, 3 (8%) from orthopaedics, 3 (8%) from general practice (GP), 3 (8%) from paediatrics/paediatric surgery, 2 (5.5%) from ophthalmology, 1 (2.7%) from ENT, 1 (2.7%) from plastic surgery, 1 (2.7%) from urology and only 1 (2.7%) article was published from dental/maxillofacial surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation